2020
DOI: 10.7308/aodontol/2020.56.e11
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre excesso de peso corporal e experiência de cárie dentária em estudantes do município de Barcelos, Amazonas, Brasil: um estudo transversal

Abstract: Objetivo: Verificar associação da prevalência da baixa estatura corporal e excesso de peso com aexperiência de cárie dentária em crianças e adolescentes, matriculados no ensino fundamental e da redepública de ensino. Métodos: Estudo transversal observacional, aprovado com o Parecer nº 197/2012 do Comitê de Éticaem Pesquisa e assinatura dos termos de consentimento e assentimento livres e esclarecidos das 1.090crianças e adolescentes, entre cinco e dezessete anos da rede pública de ensino em Barcelos, AM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Tw e n t y -t h r e e s t u d i e s t e s t e d t h e association bet ween overweight and dental caries. 12,36,29,30,32,34,35,37,39,43,44,47,48,52,53,[55][56][57][58][59][60][61]66 Of these, 21 found no association between the two variables investigated in children/adolescents. 12,36,29,30,32,34,37,39,[43][44][45]48,[51][52][53][56][57][58][59][60]66 Three studies concluded that overweight children/ adolescents were less likely to exhibit dental caries than their normal weight peers.…”
Section: Results Of Individual Studies Overweight Vs Dental Cariesmentioning
confidence: 94%
See 4 more Smart Citations
“…Tw e n t y -t h r e e s t u d i e s t e s t e d t h e association bet ween overweight and dental caries. 12,36,29,30,32,34,35,37,39,43,44,47,48,52,53,[55][56][57][58][59][60][61]66 Of these, 21 found no association between the two variables investigated in children/adolescents. 12,36,29,30,32,34,37,39,[43][44][45]48,[51][52][53][56][57][58][59][60]66 Three studies concluded that overweight children/ adolescents were less likely to exhibit dental caries than their normal weight peers.…”
Section: Results Of Individual Studies Overweight Vs Dental Cariesmentioning
confidence: 94%
“…12,36,29,30,32,34,37,39,[43][44][45]48,[51][52][53][56][57][58][59][60]66 Three studies concluded that overweight children/ adolescents were less likely to exhibit dental caries than their normal weight peers. 47,55,61 Obesity vs. dental caries Twenty-three studies tested the association between obesity and dental caries. 36,29,30,32,34,37,39,40,[43][44][45][46]48,[51][52][53]55,[57][58][59][60]63,65 Of these, 18 found no associat ion bet ween these two variables investigated in children/ adolescents.…”
Section: Results Of Individual Studies Overweight Vs Dental Cariesmentioning
confidence: 99%
See 3 more Smart Citations